The fourth ecology: Hikikomori, depressive hedonia and algorithmic ubiquity - Gray, Chantelle; Eloff, Aragorn (South African journal of philosophy, 2023)
In this article we expand upon the conceptual framework of Félix Guattari's 1989 essay, The Three Ecologies. Here Guattari examines changes in subjectivity that have come about due to scientific and technological advances which, as he sees it, brought about an "ecological disequilibrium" ([1989]2000, 27) and deteriorated individual and collective modes of being. In response to this Guattari proposes a kind of holistic therapy or 'ecosophy' between three ecological registers: "the environment, social relations and human subjectivity" (ibid., 28). Guattari cautions that we not only take note of these macro determinations, but also heed the libidinal impulses of desire - what captures it, what directs it, and what shuts it down. Since the publication of The Three Ecologies, the rise of digital technologies has dramatically influenced the ways in which people think, live and communicate. Technological infrastructures, for instance, are used to spread disinformation at a vast speed and scale, and because social networks are often homophile many people infrequently encounter critical disagreement and debate. The increase in media and digital communications usage has also led to new forms of social inclusion and exclusion, the most exacerbated form of which is probably the phenomenon known as hikikomori - acute, prolonged social withdrawal. Taking hikikomori as our focus, we describe what we see as a general set of symptoms of society and trace its myriad intersections with an ever-increasing algorithmic ubiquity, which we posit as the new form of hyper-modulation following from Foucault's disciplinary societies and Deleuze's control societies.